The Effectiveness of Implementing Criminal Sanctions as the Last Resort (Ultimum Remedium Principle) in Excise Crimes as an Effort to Recover State Revenue Losses - Munsir, David; Fahmal, A. Muin; Ahmad, Kamri (Fakultas Hukum, Universitas Muslim Indonesia, 2025)
The application of the ultimum remedium principle in excise-related criminal acts, particularly in the tobacco product sector, reflects a shift towards a more proportional and restorative approach in Indonesian criminal policy. This principle prioritizes administrative and civil measures before resorting to criminal sanctions, aiming to balance law enforcement objectives with economic stability and business sustainability. In the context of tobacco excise, the ultimum remedium approach has been utilized to minimize the negative impacts of excessive criminalization on the national economy, especially on the tobacco industry which significantly contributes to state revenue and regional employment. By implementing administrative sanctions, such as fines or permit revocations, as initial enforcement measures, law enforcement authorities can provide an opportunity for compliance improvement without immediately imposing imprisonment. However, in cases of repeated violations or severe breaches, criminal sanctions remain applicable as a deterrent. This approach aligns with restorative justice principles and supports the optimization of tax revenue collection while preserving fairness and legal certainty. The study underscores that the success of applying the ultimum remedium principle depends on clear regulatory frameworks, consistent enforcement, and inter-agency coordination. Ultimately, this policy serves as a strategic instrument in harmonizing fiscal policy, legal enforcement, and socio-economic interests within Indonesia’s excise regime